Bisphenol AF elevates procoagulant platelets by inducing necroptosis via RIPK1-inflammasome axis. (30th April 2021) - Vishalakshi, Gopalapura J.; Hemshekhar, Mahadevappa; Sandesha, Vaddaragudisalu D.; Prashanth, Kunthurumole S.; Jagadish, Swamy; Paul, Manoj; Kemparaju, Kempaiah; Girish, Kesturu S.
Abstract: Bisphenol AF, an analogue of Bisphenol A, is an important raw material used in the production of plastic and rubber substances like plastic bottles and containers, toys, and medical supplies. Increased contamination of air, water, dust, and food with BPA/BPAF, poses an enormous threat to humans, globally. BPAF/BPA are endocrine-disrupting chemicals that mimic estrogen hormone, thus increasing the risks of various metabolic and chronic disorders. Exposure of human blood cells to BPA/BPAF induces oxidative stress and genotoxicity. However, its effects on platelets, which play central roles in hemostasis and thrombosis, are not well-documented. In this study, we demonstrate that BPAF induces RIPK1-inflammasome axis-mediated necroptosis in platelets, increasing procoagulant platelet levels in vivo and in vitro . We also show that BPAF-induced rise in procoagulant platelets worsens pulmonary thromboembolism in vivo . The elevated procoagulant platelets are shown to increase platelet-neutrophil/monocyte aggregates that mediate pathogenesis of CVD, thrombosis, and chronic inflammatory diseases. Our results demonstrate the toxic effects of BPAF on platelets and how it propagates the clinical complications by elevating procoagulant platelet numbers. Altogether, our study sends a cautionary message against extensive use of BPAF in the plastic and rubber industries, resulting in frequent human exposure to it, thus endangering platelet functions.